Efektivitas Penggunaan Sistem Informasi Manajemen Al Amili dalam Pengelolaan Dana ZISKA - Zulfikar Ali Ahmad; Ivan Diva Al Mustova; Asiah Wati; Haq Muhammad Hamka Habibie (Jurnal Ekonomi Islam, 2026)
This study discusses the usage and effectiveness of the Al Amili SIM in the management of ZISKA funds at LAZISMU, Sukoharjo Regency. The purpose of this study is to find out the usage of Al Amili and how effective it is. This research uses primary and secondary data sources. Data collection techniques with interviews, observations, and documentation. Data analysis with data collection, data reduction, data presentation, and drawing a conclusion.  The results of the study show that the use of SIM Al Amili is in accordance with the provisions of the Standard Operating Procedures of LAZISMU Central Java Province. Based on the perspective of the Technology Organization Environment theory, the use of SIM Al Amili at LAZISMU Sukoharjo Regency is effective because users feel that it is very helpful and facilitates the process of processing financial data from the beginning of collection and distribution, as well as its use is more flexible.